NIHILISME DALAM FILM A CLOCKWORK ORANGE KARYA STANLEY KUBRICK - Prabowo, Bayu Ade (HUMANIKA, 2017)
This study with the title Nihilism in the Stanley Kubrick’s film A Clockwork Orange aims to reveal the meaning of the signs in the film. The source of the study is A Clockwork Orange film which directed by Stanley Kubrick. This study use semiotics approach and this study focuses on the signs in the movie which relate to nihilism. The result of this study is revealing the music Symphony No. 9th by Ludwig van Beethoven as the primary signifier. These music relate to the nihilism as the character of Alex De Large. This study also reveal the signs that relate to the nihilism and it also reveal that A Clockwork Orange movie as an illustration of nihilism that happened in the England in 1960s.